Analysis of the Influencing Factors of Higher Vocational Students' Learning Ability in the Information Age - Wang, Xiaoxue; Jiang, Yongzhi (Journal of Roi Kaensarn Academi, 2023)
Learning ability is an important indicator to measure whether a person can better deal with the development characteristics and situation of the Times, including information, knowledge update and post change, and plays an important role in the growth and development of contemporary vocational college students. This paper takes contemporary vocational college students as the research object, based on the theoretical basis and analysis in the early stage, and discusses the important influence on learning ability from four factors, such as learning habit, learning motivation, learning environment and learning attitude. After research and analysis, it is found that there are different positive relations between the four influencing factors of learning ability and learning ability, and the significant degree of influence is: learning motivation, learning habit, learning environment and learning attitude.